A facile synthesis of reduced Co3O4 nanoparticles with enhanced Electrocatalytic activity for oxygen evolution. (10th August 2016) - Liu, Yan-Ru; Han, Guan-Qun; Li, Xiao; Dong, Bin; Shang, Xiao; Hu, Wen-Hui; Chai, Yong-Ming; Liu, Yun-Qi; Liu, Chen-Guang
Abstract: Novel reduced Co3 O4 nanoparticles as electrocatalyst have been synthesized by a facile NaBH4 reduction treatment. Microwave-assisted Co3 (CH3 COO)5 (OH) has been used as precursor to increase the surface area of Co3 O4 . The as-prepared samples were characterized by X-ray diffraction (XRD), Transmission electron microscope (TEM) and scanning electron microscope (SEM). The original Co3 O4 (OCo3 O4 ) nanoparticles have been prepared by annealing of Co3 (CH3 COO)5 (OH). After treatment by NaBH4, OCo3 O4 transforms into the reduced Co3 O4 (RCo3 O4 ). Electrochemical measurements for oxygen evolution reaction (OER) show that RCo3 O4 has more excellent electrocatalytic activity with the lower onset potential of 1.5 V (vs. RHE) and larger current density by over 6.4 times than that of OCo3 O4, which may be ascribed to the more oxygen vacancies derived from reduction treatment of NaBH4 . Therefore, increasing the number of oxygen vacancies of metal oxides by facile reduction treatment may be a promising way to prepare the efficient electrocatalysts for OER. Graphical abstract: Highlights: Reduced Co3 O4 (RCo3 O4 ) was synthesized by a facile NaBH4 reduction treatment. RCo3 O4 has the enhanced OER activity owing the increasing of oxygen vacancies. Increasing oxygen vacancy provides a new way to prepare efficient electrocatalyst.